Association of Angiotensin Converting Enzyme I/D and α-actinin-3 R577X Genotypes with Growth Factors and Physical Fitness in Korean Children - Kim, Kijin; Ahn, Nayoung; Cheun, Wookwang; Byun, Jayoung; Joo, Youngsik (The Korean journal of physiology & pharmacology, 2015)
This study analyzed the differences in aerobic and anaerobic exercise ability and growth-related indicators, depending on the polymorphism of the ACE and the ACTN3 genes, to understand the genetic influence of exercise ability in the growth process of children. The subjects of the study consisted of elementary school students (n=856, age 10.32±0.07 yr). The anthropometric parameters, physical fitness and growth factors were compared among groups of the ACE I/D or the ACTN3 R577X polymorphisms. There were no significant differences between the anthropometric parameters, physical fitness and growth factors for the ACE gene ID or the ACTN3 gene R577X polymorphism. However, the DD type of ACE gene was highest in the side step test (p<0.05), and the DD type was significantly higher than the II+ID type (p<0.05) in the early bone age. The combined group of the ACE gene II+ID and the ACTN3 gene XX type significantly showed lower early bone age (p< 0.05). This study did not find any individual or compounding effects of the polymorphism in the ACE I/D or the ACTN3 R577X polymorphisms on the anthropometric parameters, physical fitness and growth factors of Korean children. However, the exercise experience and the DD type of the ACE gene may affect the early maturity of the bones.